Recommendations for Effective Co-Management Model of Small-Scale Grouper (Serranidae) Fishery in South Sulawesi Province - Raazy, Alief Fachrul; Idrus, Rijal; Demmalino, Eymal B. (Hasanuddin University, 2023)
Governance (policy) that regulates fisheries resources needs to involve industry in the supply chain (market) and small-scale grouper fishermen (community) within a co-management framework so that management is more effective while simultaneously supporting the Fisheries Improvement Project (FIP) which is driven by various parties globally (Conservation Alliance, 2021). This study aims to recommend a small-scale grouper fishery co-management model to be carried out in South Sulawesi Province. This study diagnoses the readiness (enabling condition) and willingness (motivation) of stakeholders so that they can be applied and implemented consistently (implementation). The results of this study indicate that the main approaches and strategies for the co-management model of small-scale grouper fisheries include (a) Optimizing the role of the market that promotes traceability and improving governance through a supply chain approach, (b) Synergy and synchronization of the role of government at all levels through an approach technocratic, (c) Strengthening fishermen and local institutions through a participatory approach, (d) Gathering multi-stakeholder support and collaboration through a collaborative approach. The recommended roadmap for small-scale grouper co-management in South Sulawesi Province includes three main stages, namely: (a) Initiation Stage: Commitment, Support, and Organizing, (b) Acceleration Stage: Joint Committee and Co-management Prototype, and (c) Stage Institutionalization: Scaling up and Organizing Fishermen's Forums.